An exploratory study on the factors influencing the parenting style choices of parents/caregivers enrolled in a parenting programme in Delf - Mukoni, Benita (Department of Social Development, 2023)
This research study sought to identify the parenting styles employed by parents/caregivers enrolled in a parenting programme conducted by a non-profit organisation named Sakha Isizwe Development Organisation in the Delft community, as well as the various factors that influenced their parenting styles. Additionally, the study sought to gauge the effectiveness of Sakha Isizwe Development Organisation's parenting programme which was achieved in the form of a minor programme evaluation. This research study employed a qualitative research methodology and made use of semi-structured interviews to elicit the data required to fulfil the desired objectives. The study population comprised 82 parents/caregivers enrolled in Sakha Isizwe Development Organisation's Parenting Programme, and from there a sample of 20 female parents/caregivers were selected using simple random sampling. Additionally, the sample included a combination of biological parents and social parents/caregivers such as grandmothers and aunts. Research findings revealed that the vast majority of the parents/caregivers enrolled in Sakha Isizwe Development Organisation's parenting programme employed an authoritative approach to child rearing with the exception of one participant who displayed more authoritarian tendencies. These findings can be attributed to the participant's upbringing which was a key factor in influencing their parenting style, followed by child temperament. Additionally, the participants' reported that Sakha Isizwe Development Organisation's parenting programme positively influenced their parenting practices as they described an improvement in their relationships with their children. Moreover, the participants demonstrated a shift in their beliefs and practices surrounding parenting as they had discarded their former practices for more proactive practices, such as non-punitive discipline methods, recommended by Sakha Isizwe Development Organisation. Lastly, recommendations were provided to various stakeholders, including Sakha Isizwe Development Organisation, similar establishments conducting parenting programmes, and government. These recommendations include establishing interventions directed at facilitating family reconciliation, supporting parents of troubled adolescents, increasing efforts directed at recruiting more fathers into their parenting programmes, and addressing the absent father phenomenon plaguing low-income communities in South Africa.